PENDIDIKAN KESEHATAN TENTANG PENCEGAHAN MUSCULOSKELETAL DISORDERS (MSDS) DAN MANAJEMEN KELELAHAN KERJA PADA PERAWAT - Fajar Amanah Ariga; Youlanda Sari; Nurul Haflah; Lilis Pujiati; Hijrah Purnama Sari Ariga (Jurnal Pengabdian Keperawatan Dan Kesehatan Holistik, 2026)
Nurses are healthcare professionals who are at risk of experiencing Musculoskeletal Disorders (MSDs) and work-related fatigue due to high physical demands, heavy workloads, and non-ergonomic working postures. This Community Service Program aimed to improve nurses' knowledge and skills regarding the prevention of MSDs and fatigue management at Sundari General Hospital. The program was conducted through health education sessions, discussions, and stretching exercise practices involving 15 nurses. Evaluation was carried out using pre-test and post-test assessments. The results showed an improvement in participants' knowledge, with the average pre-test score increasing from 65.3 to 88.7 in the post-test. In addition, participants were able to practice stretching techniques, ergonomic principles, and proper body mechanics correctly. This program was effective in enhancing nurses' understanding of MSD prevention and fatigue management and is expected to support occupational health, work productivity, and the quality of nursing care services.